Assessment of the Effectiveness of Counseling Approaches in Character Building among Secondary School Students: A Case of Public Secondary Schools in Kinondoni Municipality, Tanzania - Mwalukisa, Grace Manase; Mwila, Prospery M.; Kitula, Paul Rapheal (Universitas Islam Bunga Bangsa Cirebon, 2025)
Counseling services play a vital role in promoting students’ holistic development by enhancing their moral, emotional, and social adjustment within the school environment. This study assessed the effectiveness of counseling approaches in character building among secondary school students in Kinondoni Municipality, Tanzania. Specifically, it examined how psychodynamic, humanistic, and client-centered counseling approaches influence students’ behavior and personal growth. A mixed-method research design was used, integrating quantitative surveys and qualitative interviews among 528 participants, including teachers, students, school heads, and parents. Descriptive statistics and thematic analysis were used to analyze the data. The findings revealed that counseling significantly contributes to students’ discipline, emotional regulation, and interpersonal relationships; however, its impact is hindered by insufficient resources, limited professional training, and low administrative support. The study recommends that counseling services be strengthened through capacity building, dedicated facilities, and policy integration to promote sustainable character development among students.